Paediatric Cushing's syndrome: epidemiology, investigation and therapeutic advances. - Storr, H; Chan, L; Grossman, AB; Savage, M (2007)
Cushing's syndrome (CS), which is caused by excessive circulating glucocorticoid concentrations, is rare in the paediatric age range but presents a diagnostic and therapeutic challenge. Most paediatric endocrinologists have limited experience of managing children or adolescents with CS and thus benefit from close consultation with colleagues who treat adult patients. A protocol for investigation is required that broadly follows the model for adult patients. Here, the epidemiology and diagnosis of different causes of CS are discussed according to typical age of presentation. Treatment strategies for adrenocorticotrophic hormone (ACTH)-independent and ACTH-dependent CS are described and critically appraised. The management of paediatric CS patients after cure also presents challenges for optimizing growth, bone health, reproduction and body composition from childhood into and during adult life.